Environmental Designs for Reading from Imaging Workstations: Ergonomic and Architectural Features - Horii, Steven C. (Springer-Verlag, 2003)

(untitled)
Despite the rapid progress made in the electronic design of imaging workstations for medicine, much less effort has gone into the design of environments in which such systems will be used. Based on studies of radiologist film reading sessions, considerable time will be spent working at such viewing systems. If the rooms in which the workstations are placed are not conducive to comfortable work, it will certainly not favor electronic viewing over film reading. In examining existing reading environments, it is also apparent that they are not optimum, even for film. Since some of the problems for film and electronic viewing overlap, such as heat generation (by the alternators, viewboxes, or workstation electronics) and glare from light sources, it should be possible to develop solutions which are applicable to both environments or to rooms which will feature both viewing systems. This paper will discuss some of the approaches to designing environments in which viewing of images is supported by the room architecture and engineering and not degraded by it. To illustrate these points, a design based on the constraint of a real room size and available architectural materials will be developed.